A case of chickenpox with multiple bacterial complications requiring surgical treatment - O. V. Molochkova; O. B. Kovalev; P. Yu. Luzan; N. O. Ilyina; Sh. A. Ganiev; A. K. Konovalov; O. V. Shamsheva; N. Yu. Egorova; A. D. Zotova; A. L. Rossina; A. A. Korsunskiy; E. V. Galeeva; et al. (LLC "Diagnostics and Vaccines", 2022)
Chickenpox is a controlled infection, even a single vaccination effectively prevents the development of severe forms (up to 98%).Purpose - to demonstrate a case of severe chicken pox in a child aged 3.8 years with secondary infection of the skin of the right subscapular region and subcutaneous fat (phlegmon of the trunk) of streptococcal etiology.The diagnosis of varicella was confirmed by the detection of Varicella-Zoster virus DNA by PCR from the skin. Surgical treatment was performed - opening and drainage of phlegmon, purulent-serous discharge was obtained, sowing was performed, Streptococcus pyogenes was isolated.The child received antibiotic therapy - cefepime sulbactam, amikacin, acyclovir, infusion therapy, local treatment.Conclusions. The given clinical case demonstrates the development of a severe bacterial complication of chicken pox, which required surgical treatment and substantiates the need for vaccination against chicken pox and its possible complications.